Pelaksanaan peruntukan perlindungan dan kebajikan kanak-kanak menurut Undang-Undang Keluarga Islam di Malaysia: Kajian dari perspektif Konvensyen Hak Kanak-Kanak 1989 / Nor'asyikin Hamzah - Nor'asyikin , Hamzah (2018)
Convention on the Rights of the Child 1989 is an international treaty of United Nation. Malaysia has ratified the treaty in 1995 with reservation on several articles until today. This convention binds state party to ensure any state laws which relate to child welfare and protection under the Convention will be abided except for the reserved articles. Therefore, this qualitative research thesis attempted to investigate the implementation of provisions relating to child welfare and protection under the Islamic Family Law in Malaysia meets the Convention standard. Data of this study were collected through library research and field work while qualitative descriptive analysis was employed for data analysis. The most significant finding shows that majority of the Malaysian Islamic Family Law (MIFL) implementation related to childrens‟ protection and welfare do meet the standard of the Convention. Unfortunately, there area few of privisions and implementation that relate to a child out of wedlock‟s right to claim for filiation on the paternal side, maintenance and custodial rights do not meet the Article 2 (no discrimination) of the Convention. This is due to the provisions are contradict to the Hukum Shara‟, whereas MIFL has to abide the Hukum Shara‟. Another finding shows the attitude some of parents in selected cases whom less attentive in upholding their childrens‟ welfare even though the selected Shariah Court provided them chances to implement it.